1984
DOI: 10.1042/bj2240581
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and chemical and immunochemical characterization of the peanut-lectin-binding glycoprotein from human milk-fat-globule membranes

Abstract: Membrane glycoprotein with high Mr (HMr-MGP) was purified from neuraminidase-treated Triton X-100-solubilized human milk-fat-globule membranes by peanut-agglutinin (PNA) affinity chromatography. The high carbohydrate content (75%), blood-group-A activity and typical monosaccharide composition (L-fucose, D-galactose, N-acetyl-D-glucosamine and N-acetyl-D-galactosamine in the proportions 0.26:1.00:1.85:1.30) indicate that the isolated HMr-MGP is a mucinous substance. Fractionation of the oligosaccharides from al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…According to this particular property, mucins which are found in human secretions or in epithelial membranes are suitable candidates for representing organ-characteristic glycosylation and thus express a variety of receptor-analog structures for bacterial adhesins. Mucins are regular constituents of human milk serum (19) and HMFGM (13). The common structural unit of all acidic glycans on secretory milk mucins is the terminal disaccharide unit NeuAcot-(2-3)-GalI, which has been demonstrated to form a receptor analog for S-fimbriated E. coli (22).…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this particular property, mucins which are found in human secretions or in epithelial membranes are suitable candidates for representing organ-characteristic glycosylation and thus express a variety of receptor-analog structures for bacterial adhesins. Mucins are regular constituents of human milk serum (19) and HMFGM (13). The common structural unit of all acidic glycans on secretory milk mucins is the terminal disaccharide unit NeuAcot-(2-3)-GalI, which has been demonstrated to form a receptor analog for S-fimbriated E. coli (22).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The membrane surrounding the lipid core is derived from the apical plasma membrane of mammary epithelial cells by apocrine secretion (11,12). High-molecular-mass glycoproteins with a high content of 0-glycosidic-linked carbohydrates (termed mucins) are a major constituent of these membranes (7,13,41). As these human milk fat globule membranes (HMFGM) are of epithe-lial origin, we expected them to express carbohydrate structures that might serve as receptor analogs for certain pathogenic bacteria.…”
mentioning
confidence: 99%
“…(1986) have reported a further high-M, component present in HMFG membranes (approx. 550,000) which may be more similar to gp580 than PAS-0, as may the high Mr glycoprotein, also isolated from HMFG (Fischer et al, 1984). Differences in distribution of PAS-0 and gp580 are suggested by the fact that we did not detect significant immunoreactivity of MAb GP2156 with normal rat mammary tissue (data not shown).…”
Section: Not Determinedmentioning
confidence: 74%
“…We view evidence of their human diversity in the MFG as a forerunner of what may be revealed in other tissues and cells. Fischer et al [13] have reported that both peanut agglutinin and polyclonal antibodies to the HM, glycoproteins of human MFGs bind to apical membranes of fundic glands in gastric mucosa, distal tubuli of human kidney, cells of histiocytic origin and some mammary carcinomas. A band of glycoprotein comigrating on SDS gels with those in our 4% gel (figs 1 and 2) has been detected in plasma membrane from porcine intestinal mucosal cells (Patton, S. and Patton, J.S., unpublished).…”
Section: Discussionmentioning
confidence: 99%